To study duration of viral clearance in COVID 19 patients: A Prospective study from Bangalore, India - Rajoli, Swetha; Rajanna, Avinash Hanbe; Yadav, Sumesh (Asian Journal of Medical Sciences, 2021)
Background: COVID-19 infection, which first reported as a cluster of pneumonia from Wuhan, China, in December 2019, has rapidly emerged as a global pandemic. During the early course of the pandemic. The duration of infectious virus replication is an important factor for clinicians. There is a significant correlation between the duration of SARS-CoV-2 virus clearance and the prognosis of COVID-19. Aims and Objective: To study Duration of viral clearance in COVID 19 patients, admitted in an Indian setting. Materials and Methods: The prospective single-center study considered adults patients of both the gender, diagnosed with COVID-19 infection by RT-PCR technique. Necessary demographic and clinical data were collected and selected subjects were followed-up until discharge or death. Based on the number of days required for viral clearance, the subjects were classified as: group 1: ≤ 14 days, group 2: 15-28 days, and group 3:>28 days. Results: The study included 536 patients it was found that mean duration required for viral clearance was around 8.98±3.54. Mean ages noted for group1, 2 and 3(based on viral clearance) were 37.57±13.65 years, 37.12±13.73 years and 49.50±23.56 years respectively. There was a significant difference between mean age of group 1 and 2, as well as group 1 and 3. Moreover, the distribution of patients across different age group was found to be statistically significant (P<0.05). Significant difference was noted between three groups with respect to the comorbidity status (P<0.0001). The COVID-related symptoms dyspnea and cough were more prominent in group 3 (P<0.05). TLC which is statistically significant (p<0.05), lower the TLC more the duration of viral clearance and more the duration of hospital stay. Conclusion: The mean days of viral clearance noted in COVID subjects is around 8.98±3.54 days. There was a significant difference between mean age of group 1 and 2, as well as group 1 and 3. However, there is no statistically significant correlation between duration of hospital stay and inflammatory markers except TLC which is statistically significant (p<0.05), lower the TLC more the duration of viral clearance and more the duration of hospital stay.